The influence of Marketing Mix (4P) on consumer repurchase intention of AMDK X mediated by brand image and consumer attitude - Clara Felicia; Theresia Gunawan (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effects of the marketing mix, comprising product, price, place, and promotion, on repurchase intention, with brand image and consumer attitude serving as mediating variables in the context of a high-pH bottled drinking water brand in Indonesia. A quantitative explanatory research design was employed using purposive sampling, with data collected from 100 valid respondents through a five-point Likert-scale questionnaire. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that promotion and consumer attitude have positive and significant effects on repurchase intention. Furthermore, consumer attitude significantly mediates the relationships between product, price, and promotion and repurchase intention, whereas brand image does not exhibit a significant mediating effect. These findings highlight consumer attitude as the primary mechanism through which marketing mix strategies influence repurchase intention. This study contributes to the consumer behavior and marketing literature by clarifying the mediating roles of consumer attitude and brand image in repurchase decisions within the bottled water industry. The findings also provide practical implications for marketers by emphasizing the importance of strengthening positive consumer attitudes through effective product, pricing, and promotional strategies to encourage repeat purchases. Keywords: Marketing Mix; Brand Image; Customer Attitude; Repurchase Intention